2008
DOI: 10.1177/172460080802300305
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B, Cathepsin H, Cathepsin X and Cystatin C in Sera of Patients with Early-Stage and Inflammatory Breast Cancer

Abstract: Numerous studies have linked cathepsins and their inhibitor cystatin C to tumor invasion and metastasis. We examined whether cathepsin B, cathepsin H, cathepsin X and cystatin C could be detected in sera from women with earlystage or inflammatory breast cancer and whether they correlated with clinicopathological characteristics. Preoperative serum was obtained from 176 patients with early-stage breast cancer (tumor size ≤5 cm, negative lymph nodes) and 31 patients with inflammatory breast cancer. Cathepsin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 33 publications
1
28
1
Order By: Relevance
“…As shown by our group, significantly lower levels of active Cat X were found in serum of patients with inflammatory breast cancer compared to non-inflammatory breast cancer 22. In cyst fluid from epithelial ovarian cancer we did not find a significant correlation of the levels of active Cat X with any clinico-pathological parameter 23.…”
Section: Introductioncontrasting
confidence: 42%
“…As shown by our group, significantly lower levels of active Cat X were found in serum of patients with inflammatory breast cancer compared to non-inflammatory breast cancer 22. In cyst fluid from epithelial ovarian cancer we did not find a significant correlation of the levels of active Cat X with any clinico-pathological parameter 23.…”
Section: Introductioncontrasting
confidence: 42%
“…Cathepsins, a specific class of lysosomal enzymes, have been shown to be significantly involved in mediating the inflammatory response and cholesterol trafficking464748. Furthermore, we have recently reported that plasma CatD was strongly associated with pediatric NASH11.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, it is believed that CysC played a negative role in cancer invasion and migration, at least in some types of cancers. However, some other studies indicated that high serum CysC level was related with poor prognosis and it could promote the progression of several cancers [24, 30]. Moreover, cathepsin B, one of major cathepsins inhibited by CysC, was demonstrated to be a protease with caspase-processing activity and an pro-apoptotic and –inflammatory cathepsin member [6, 31].…”
Section: Discussionmentioning
confidence: 99%